An Insight into México Art’s Symbolic Value through their Economic Behavior: One Case of Valuation Comparison Between the Emergent Physical and Digital Abstract Art Market, 2021 - Cortés Enriquez, Luis Armando; Camarena Tolentino, Francisco Josue; Roa Aguiar, Valeria (Integrated Journal for Research in Arts and Humanities, 2024)
This work analyzes the phenomenon of the symbolic value in digital art over the circuit NFT in México, considering the economic behavior as a factor to identify their dynamics and characteristics, but at the same time, to recognize their influence and capacity of change from the interaction of the hybrid spaces that have this new kind of artist and pieces of work; to rethink from there, the traditional considerations for the symbolic value to looking at how to be modified in their relation with the circuit of NFT art. This makes it possible to propose an experimental aesthetic economic methodology to compare their different behaviors positions and structures, this time, in the particular case of two artists, who have different stays of symbolic value and activities in the traditional formats and digital art. Access and review of the hybrid quantitative (financial) and qualitative (trajectories and aesthetic) information, allowed the identification of meeting points, disagreement zones, and new spaces of analysis of these phenomena, to bring to the broad new considerations in the symbolic value, that is to say, new variables to consider in the dynamic values in the different kind of productions of our times.